Kinetic Based Simulation of Methane Steam Reforming and Water Gas Shift for Hydrogen Production Using Aspen Plus - Mohamad Rizza, Othman; Arshad, Ahmad; Umarul Imran, Amran (Italian Association of Chemical Engineering - AIDIC, 2017)
This paper presents the kinetic-based simulation of methane steam reforming (MSR) from natural gas and water gas shift (WGS) reaction for hydrogen production. It is found that most simulations of these reactions were either done as balance or equilibrium based. Although it provides simplicity, such approach has limitations, especially for sensitivity analysis, control and optimisation. In order to improve and optimise the reactor performance, kinetic-based simulation is necessary. The kinetic data for MSR and WGS reactions were obtained from literature. The simulation was performed in Aspen Plus using RPLUG model blocks with rearranged Langmuir-Hinshelwood-Hougen-Watson (LHHW) kinetic model. The results of the simulation show good agreement with results found in the literature. Apart from that, sensitivity analysis was carried out to observe the effect of several parameters such as temperature, pressure, catalyst weight and ratio feed to the reactor performance.